Modelo Prolab: Bloqueador solar orgánico - Morales Riva, Miguel Angel (2025)
This study addresses a critical issue faced by plantation workers in agricultural companies in Peru, who are responsible for harvesting organic fruits under harsh weather conditions, particularly prolonged exposure to solar radiation. Although these companies provide basic sun protection equipment, it is often uncomfortable and fails to offer enough protection against ultraviolet radiation. Importantly, chemical sunscreens are not provided to avoid contaminating organic produce, which is essential for the market these companies serve. Recognizing this need, we propose SOLARBLOK, an organic sunscreen made entirely from natural ingredients, primarily seaweed extracts and organic oils. SOLARBLOK not only protects workers' skin, enhancing their health and quality of life, but also ensures no contamination of the organic fruits being harvested. The economic feasibility of SOLARBLOK has been demonstrated with a Net Present Value (NPV) of S/3’909,736.67, an Internal Rate of Return (IRR) of 98% a Benefit/Cost ratio of 8.43, and a payback period of 2.22 years with an initial investment of S/526,412.66. These indicators highlight the project's financial soundness and its alignment with the United Nations Sustainable Development Goal (SDG) 3, "Good Health and Well-being," promoting well-being for all ages. SOLARBLOK's business model is based on a 100 ml bottle produced from locally sourced raw materials, reinforcing its commitment to sustainability and social responsibility. With a Social Relevance Index (SRI) of 15% and a Social Net Present Value (SNPV) of S/7’053,316.45, the project is confirmed to be not only viable and profitable but also a significant contributor to social and environmental well-being.